PELATIHAN DASAR ROBOTIKA UNTUK SISWA SMAN 26 BATAM - Candra, Joni Eka Candra; Jufri, Mohammad; Aranski, Alvendo Wahyu; Abrar, Mohammad Masril; Noviardi, Refli; Nasution, Nadia Widari; Burhan, Rifatul Mahmudah (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
Batam 26 High School or known as Smandanam is a superior school which aims to produce a generation with knowledge and superior character. whose address is at the Botania 1 Complex, Botania Garden Batam Center Batam City, where currently SMAN 26 Batam is led by Mr. Midiyanto, S.PD., M.M as Principal of the School. At SMAN 26 Batam, currently there are two main focus areas: the Department of Natural Sciences (IPA) and the Department of Social Sciences (IPS). Given the importance of digital technology and automation in both domestic and industrial settings, it is important to include robotics curricula from elementary to high school, even though they are currently offered as extracurricular activities. The most important aspect of the Community Service program is the potential for sustainability. This program can be continued with a mentoring program in the development of extracurricular curriculum at SMAN 26 Batam, namely by assisting in making different types of mobile robots. The method that will be used is the method of providing mobile robot materials and will briefly present the steps for assembling a mobile robot. Furthermore, participants will try out the assembled results in the field or object work line. On this occasion the PengMas team will help provide training on assembling mobile robots. This robotics training activity provides an opportunity for students and teachers to become more familiar with basic computer programming and furthermore, participants will have the skills to assemble robots.